EXPERIMENTAL INVESTIGATION ON ELECTROCHEMICAL MACHINING PARAMETERS - Dhia Ahmed Alazawi (Diyala Journal of Engineering Sciences, 2017)
The inherent characteristics of electrochemical machining (ECM) have large scale of advantages over the traditional machining technologies. ECM has been employed in this work to machining low carbon AISI1005 steel. Such technique is used to remove the electrical conductive material via a controlled electrochemical anodic reaction regardless of the metal mechanical properties. The considered experiments were conducted to study the effects of process parameters such as applied voltage, electrolyte flow rate, current density on all of weight loss, dissolution rate and material removal rate (MRR) in sodium chloride aqueous solution. The results stated that, the weight loss is in general increased with the voltage and the flow rate as its maximum value was 9.23 g and 5.35g respectively. Increasing the current density has led to obtain maximum MRR and dissolution rate of 0.248g/min and 1.59 mm/min respectively. The results showed that there was an enhancement in the MRR and the dissolution rate so as to be 66.8% and 3.94% respectively.